2023
DOI: 10.30596/rmme.v6i1.14219
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Data Sintetis dalam Simulasi Kinerja Mesin Pemipil Jagung

Abstract: Corn sheller machine simulation is a process of modeling the performance of corn sheller machines in a virtual environment using software. The purpose is to predict machine performance, test and improve machine design before mass production, and minimize development cost and time. This study conducted a simulation of corn sheller machine performance comparison using real and synthetic data, by simulating the input of 1000 kg of cobbed corn mass. Synthetic data was created using linear interpolation method usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The design of a digital literacy based website aims to improve the understanding and knowledge of mechanical engineering students at Universitas Muhammadiyah Sumatera Barat, based on the results of a field survey conducted among mechanical engineering students at Universitas Muhammadiyah Sumatera Barat. The survey revealed that the students' level of understanding of digital literacy, especially in the field of mechanical engineering, is still minimal, including their knowledge of software or applications that can facilitate their research on their final project (thesis) [5]. This is reflected in the research results of the students who always refer to the research titles created by their previous seniors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of a digital literacy based website aims to improve the understanding and knowledge of mechanical engineering students at Universitas Muhammadiyah Sumatera Barat, based on the results of a field survey conducted among mechanical engineering students at Universitas Muhammadiyah Sumatera Barat. The survey revealed that the students' level of understanding of digital literacy, especially in the field of mechanical engineering, is still minimal, including their knowledge of software or applications that can facilitate their research on their final project (thesis) [5]. This is reflected in the research results of the students who always refer to the research titles created by their previous seniors.…”
Section: Methodsmentioning
confidence: 99%
“…The application of digital computational technology in the field of mechanical engineering can improve production process efficiency, product quality, or energy efficiency [4]. By utilizing digital technology, product design can be created faster and more accurately, machine simulation can be conducted to evaluate machine performance before being implemented in production processes [5], [6] and data analysis can be performed to improve production process efficiency. However, student knowledge is still limited to previous research conducted by their peers, resulting in a lack of innovation and courage in choosing new research topics related to digitalization in the field of mechanical engineering [7].…”
Section: N V O T E Kmentioning
confidence: 99%
See 1 more Smart Citation